2016
DOI: 10.1111/labr.12082
|View full text |Cite
|
Sign up to set email alerts
|

On Government‐Subsidized Training Programs for Older Workers

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
0
14
1
Order By: Relevance
“…The oldest age group of workers, 55 to 65 years, profits neither in terms of employment nor earnings. Thus, contrary to the findings of Dauth and Toomet (2016), who found that treatment postpones retirement for workers 55 years and older in SME, lowskilled workers above age 55 do not similarly profit from the program. This difference might be attributable to more firm-financed training for nontreated, low-skilled workers in larger firms-compared to SME-and thus a better comparison group.…”
Section: Results By Individual Characteristicscontrasting
confidence: 94%
See 3 more Smart Citations
“…The oldest age group of workers, 55 to 65 years, profits neither in terms of employment nor earnings. Thus, contrary to the findings of Dauth and Toomet (2016), who found that treatment postpones retirement for workers 55 years and older in SME, lowskilled workers above age 55 do not similarly profit from the program. This difference might be attributable to more firm-financed training for nontreated, low-skilled workers in larger firms-compared to SME-and thus a better comparison group.…”
Section: Results By Individual Characteristicscontrasting
confidence: 94%
“…Additionally, an economic stimulus package in January 2009 prompted the FEA, among others, to expand subsidized training for employees to give firms the incentive to train surplus workers instead of firing them (Möller 2010). A new law introduced a third target group for 2009 and 2010 to the existing target groups (workers in SME analyzed by Dauth and Toomet [2016] and low-skilled workers analyzed here). This new target group comprised workers who had not been funded by a public project for the previous four years and workers whose vocational degree was at least two years old ( § 421 t (4) Social Code III).…”
Section: Results By Cohortmentioning
confidence: 99%
See 2 more Smart Citations
“…Worse yet, a training voucher program in Chile actually lowered employment and earnings, although it did have a positive effect for women and mainly those with low levels of education. On the other hand, government-subsidized training for older workers in Germany improved their job stability (Hidalgo, Oosterbeek, and Webbink, 2014;Görlitz and Tamm, 2016;Kaplan et al, 2015;Dauth and Toomet, 2016). In the case of tax credit incentives offered to companies, the Chilean tax exemption program, Franquicia Tributaria, in most cases, does not improve wages and employment; only longer programs have slightly better results (Rodríguez and Urzúa, 2011).…”
Section: On-the-job Training (Ojt): Staying Competitivementioning
confidence: 99%